Shooting Athlete Mental Training - Arief Ibnu Haryanto; Ardin Abdul Gani; Gilang Ramadan; Giofandi Samin; Iwan Fataha; Sulasikin Sahdi Kadir (JUARA : Jurnal Olahraga, 2021)
This study aims to determine the effect of meditation practice and internal imagery on the concentration and shooting accuracy of the 10-meter category in the Perbakin Bantul branch. The research method was experimental with a two-group pretest-posttests design. The population investigated 16 athletes using the purposive sampling technique so that the sample became 12 athletes. The research instrument used the Grid Concentration Exercise to measure concentration and measurement of firing accuracy using ISSF standard target targets. The data analysis technique used was paired t-test and independent t-test. The results showed an effect of training between autogenic meditation and internal images on concentration and shooting accuracy. When viewed from the percentage increase, the meditation practice method showed better results than internal imagery, while internal imagery training showed better results in increasing concentration.